Performance of village facilitators in sustainable community empowerment - Isra Djabbar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
This study aimed to analyze and describe the performance of village assistants in sustainable community empowerment activities in Lalonaha Village, Wolo District, Kolaka Regency. Qualitative descriptive research method. Data obtained through interviews, literature study, and observation. The data analysis stage uses the Miles and Huberman method, namely data collection, data presentation, data verification, and concluding. Based on the research results, village assistants' capability in its implementation has not optimally because there are still many priority programs that people should expect but have not implemented. Activities carried out by village assistants in terms of development implementation, development supervision, and village administration training carried out by village assistants in Lalonaha Village, Wolo District have been able to run well, it is just that the obstacles faced regarding the quality of work by village assistants have not been able to carry out proper coordination fully. Both between the Lalonaha Village Government and the village community. In the implementation stage of village facilitator activities to help village government activities have not been able to run well, this is because in every development activity and supervision of development programs carried out more by the village apparatus themselves. The independence of village assistants in improving community empowerment in the village Lalonaha has not gone well because the village government itself carries out almost all the implementation of village assistance activities.